Hybrid Solid Polymer Electrolytes with Two‐Dimensional Inorganic Nanofillers. Issue 69 (20th November 2018) - Chua, Stephanie; Fang, Ruopian; Sun, Zhenhua; Wu, Minjie; Gu, Zi; Wang, Yuzuo; Hart, Judy N.; Sharma, Neeraj; Li, Feng; Wang, Da‐Wei
Abstract: Solid polymer electrolytes are of rapidly increasing importance for the research and development of future safe batteries with high energy density. The diversified chemistry and structures of polymers allow the utilization of a wide range of soft structures for all‐polymer solid‐state electrolytes. With equal importance is the hybrid solid‐state electrolytes consisting of both "soft" polymeric structure and "hard" inorganic nanofillers. The recent emergence of the re‐discovery of many two‐dimensional layered materials has stimulated the booming of advanced research in energy storage fields, such as batteries, supercapacitors, and fuel cells. Of special interest is the mass transport properties of these 2D nanostructures for water, gas, or ions. This review aims at the current progress and prospective development of hybrid polymer‐inorganic solid electrolytes based on important 2D materials, including natural clay and synthetic lamellar structures. The ion conduction mechanism and the fabrication, property and device performance of these hybrid solid electrolytes will be discussed. Abstract : Powering up : This Review aims at the current progress and prospective development of hybrid polymer‐inorganic solid electrolytes based on important 2D materials, including natural clay and synthetic lamellar structures. The ion conduction mechanism and the fabrication, property and device performance of these hybrid solid electrolytes are discussed.